A combination of cherry juice and cold water immersion does not enhance marathon recovery compared to either treatment in isolation: A randomized placebo-controlled trial - Isabella Difranco; Emma Cockburn; Lygeri Dimitriou; Lygeri Dimitriou; Katherine Paice; Scott Sinclair; Scott Sinclair; Tanwir Faki; Frank A. Hills; Marcela B. Gondek; Alyssa Wood; Laura J. Wilson (Frontiers Media S.A., 2022)
PurposeCherry juice (CJ) and cold water immersion (CWI) are both effective recovery strategies following strenuous endurance exercise. However, athletes routinely combine recovery interventions and less is known about the impact of a combined CJ and CWI protocol. Therefore, this study investigated the effects of combining CWI and CJ (a "cocktail" (CT)) on inflammation and muscle damage following a marathon.MethodsA total 39 endurance trained males were randomly assigned to a placebo (PL), CWI, CJ, or CT group before completing a trail marathon run. Muscle damage (creatine kinase (CK)), muscle function (maximal voluntary isometric contraction (MVIC)), and inflammation (interleukin-6 (IL-6); C-reactive protein (CRP)) were measured at baseline, immediately after marathon (only IL-6), 24 h, and 48 h after marathon.ResultsThere were no statistically significant differences between groups and no group × time interaction effects for any of the dependent variables. Confidence intervals (CI) illustrated that CT had unclear effects on inflammation (IL-6; CRP) and MVIC, but may have increased CK to a greater extent than PL and CJ conditions.ConclusionThere is no evidence of an additive effect of CJ and CWI when the treatments are used in conjunction with each other. On the contrary, combining CJ and CWI may result in slightly increased circulating CK.